On Cavellian scepticism and postgraduate student supervision - Waghid, Y (South African Journal of Higher Education, 2011)
In this essay I offer an imaginary of postgraduate student supervision focusing on sceptical encounters with the other. Drawing on the seminal thoughts of Harvard philosopher Stanley Cavell (1997), particularly on his ideas on ‘living with scepticism’, I argue that postgraduate student supervision ought to be an encounter framed by scepticism. I point out that supervising students sceptically might engender moments of acknowledging humanity within the Other, attachment to the Other’s points of view with a readiness for departure, and showing responsibility to the Other.